VAS for assessing the perception of antihistamines use in allergic rhinitis - Ciprandi, Giorgio; La Mantia, Ignazio (Acta Biomedica Atenei Parmensis, 2019)
The quantification of the antihistamines’ consumption is particularly relevant in clinical practice, since their remarkable use is usually associated with severe symptoms. The aim of the study was to measure the visual analogue scale (VAS) for assessing the patient’s perception about antihistamines use in patients with allergic rhinitis. 103 patients (49 males, mean age 35.9 years) with allergic rhinitis due to Parietaria pollen were evaluated retrospectively. They recorded monthly the number of antihistamine tables they took during the pollen season (lasting for about 5 months). There was a strong relationship (r= 0.921 Pearson; p